Increased iNKT17 Cell Frequency in the Intestine of Non-Obese Diabetic Mice Correlates With High Bacterioidales and Low Clostridiales Abundance - De Giorgi, Lorena; Sorini, Chiara; Cosorich, Ilaria; Ferrarese, Roberto; Canducci, Filippo; Falcone, Marika (Frontiers in Immunology, 2018)
iNKT cells play different immune function depending on their cytokine-secretion phenotype. iNKT17 cells predominantly secrete IL-17 and have an effector and pathogenic role in the pathogenesis of autoimmune diseases such as Type 1 Diabetes (T1D). In line with this notion, non-obese diabetic (NOD) mice that spontaneously develop T1D have an increased percentage of iNKT17 cells compared to non-autoimmune strains of mice. The factors that regulate iNKT cell expansion and acquisition of a specific iNKT17 cell phenotype are unclear. Here we demonstrate that the percentage of iNKT17 cells is increased in the gut more than peripheral lymphoid organs of NOD mice thus suggesting the intestinal environment promotes iNKT17 cell differentiation in these mice. Increased intestinal iNKT17 cell differentiation in NOD mice is associated with the presence of pro-inflammatory IL-6-secreting dendritic cells (DCs) that promote iNKT cell expansion and iNKT17 cell differentiation. In addition, we found that increased iNKT17 cell differentiation in the large intestine of NOD mice is associated with a specific gut microbiota profile. Specifically, we demonstrated a positive correlation between percentage of intestinal iNKT17 cells and bacterial strain richness (α-diversity) and relative abundance of Bacterioidales strains. On the contrary, the relative abundance of the anti-inflammatory Clostridiales strains negatively correlates with the intestinal iNKT17 cell frequency. Considering that iNKT17 cells play a key pathogenic role in T1D, our data support the notion that modulation of iNKT17 differentiation through gut microbiota changes could have a beneficial effect in T1D.